How followers' neuroticism buffers the role of the leader in their daily mental health via daily positive affect: A multilevel approach - Junça Silva, A.; Caetano, A. (Personality and Individual Differences, 2023)
This study expands on the existing research on employees' work-related mental health by analyzing (1) the relationship between within-person fluctuations in perceived leadership effectiveness and positive affect and mental health and (2) between-person variations in neuroticism as a relevant boundary condition of this relationship. Multilevel data were collected from 224 working adults (2240 measurement occasions). The results demonstrated that fluctuations in the perception of the leader's effectiveness were positively related to daily positive affect, and this relationship was moderated by the followers' levels of neuroticism, in such a way that higher levels of neuroticism buffered the positive effect of leadership effectiveness on positive affect. The findings also evidenced a positive relationship between daily positive affect and daily mental health, as well as a significant indirect effect from perceived leadership effectiveness to daily fluctuations in mental health via daily fluctuations in positive affect. An effective leader makes employees feel more positive affect during the day, which is beneficial to their daily mental health; however, this relationship is may be impaired by the employees' levels of neuroticism. Practical implications for theory and practice are discussed.